Chronic Exposure to Continuous Brightness or Darkness Modulates Immune Responses and Ameliorates the Antioxidant Enzyme System in Male Rats - Moustafa, Amira (Frontiers in Veterinary Science, 2021)
Circadian rhythms are considered vital regulators of immune functions. This study aims to elucidate the effects of chronic circadian disruption on immune functions, clock gene expression, and antioxidant enzyme levels in lymphoid tissues. Adult male Sprague-Dawley rats were subjected to a normal light/dark cycle or either continuous light (LL) or continuous dark (DD) for 8 weeks. The results demonstrated 1) significant decreases in the circulating levels of interleukin 1β, interleukin 6 and tumor necrosis factor alpha (TNF-α) and significant increases in the levels of interleukin 10, interleukin 12, C-reactive protein (CRP) and corticosterone in both LL and DD groups; 2) upregulation in mRNA expression of core clock genes Cry1, Cry2, Per1, Per2 and Per3 in the spleen of the DD group and downregulation in Cry1 and Cry2 genes in the LL group; 3) elevation of total antioxidant capacity (TAC), superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), nitric oxide (NO) and the lipid peroxidation marker malondialdehyde (MDA) in the spleen, lymph node and bone marrow of both the LL and DD groups and decreases in the levels of the same markers in the thymus of the LL group; 4) decreased numbers of CD4+ and CD8+ cells in lymphoid tissues of both the LL and the DD groups; 5) reduced platelets count and suppressed immunoglobulin (IgM, IgE) in the LL and DD groups with marked erythropenia and leukocytosis in the DD group. Taken together, circadian misalignment leads to hematological disruptions, dysregulation of clock genes, and inflammatory mediators, which further enhances the antioxidant enzyme system that is crucial for an organism’s adaptation to stresses.